Budget impact model of indacaterol/glycopyrronium in the treatment of chronic obstructive pulmonary disease in Italy based on the FLAME study. (October 2018) - Aiello, Andrea; Ritrovato, Daniela; Pitotti, Claudia
Purpose: We aimed to estimate the 3-year budget impact of replacing salmeterol/fluticasone with indacaterol/glycopyrronium for the treatment of chronic obstructive pulmonary disease patients in Italy. Methods: The budget impact model included patients with moderate, severe, and very severe chronic obstructive pulmonary disease and was developed using data from the FLAME study. The budget impact model considered direct medical costs from the National Healthcare System perspective over a 3-year time-horizon. Costs of drugs, adverse events, and exacerbations were estimated using public net prices for drugs and national (inpatient/outpatient) tariffs for patient management. Data on adverse events and exacerbations were derived from FLAME and other clinical trials. The model assumed an increasing uptake of indacaterol/glycopyrronium, substituting it for salmeterol/fluticasone. Two sensitivity analyses were conducted. In the first, every long-acting muscarinic antagonist/inhaled corticosteroid switch to indacaterol/glycopyrronium; in the second, drugs compliance varies from 20% to 60%. Results: The target population was estimated at 572, 788 patients in the first year, increasing to 585, 491 in the third year. The alternative treatment pattern, with a higher indacaterol/glycopyrronium uptake, was associated with a total cost of €1.69 billion over 3 years, while the total costs in the current treatment pattern amounted to €1.71 billion. Thus, increasing indacaterol/glycopyrronium use provided total savings of €17.3 million over 3 years. Sensitivity analysis confirmed robustness of the results. Conclusion: Increasing the uptake of indacaterol/glycopyrronium was estimated to be cost-saving for the Italian National Healthcare System, both when drug-related expenditures and total costs were considered. Savings increased with the number of patients switching to indacaterol/glycopyrronium.